2018
DOI: 10.1080/10495398.2018.1456446
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Polymorphism in Bovine lncRNA ADNCR Gene and Its Association with Growth Traits

Abstract: Adipocyte differentiation-associated long noncoding RNA (ADNCR) is a newly discovered lncRNA. It plays function by targeting miR-204 to significantly regulates the expression of the target SIRT1 gene in preadipocytes both at the level of mRNA and protein, thereby inhibiting adipogenesis. The tetra-primer amplification refractory mutation system PCR (T-ARMS-PCR) strategy is fast and accuracy at a negligible cost for SNP genotyping in large samples. In the study, a novel SNP g.1263T>A in intron 1 of bovine ADNCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In animal breeding, it is important to explore crucial markers. In cattle, numerous variations have been identified within the protein-coding genes, but only a few studies have uncovered the variations in the non-coding RNA genes (Jin et al, 2018; Yu et al, 2018). In this study, first, we analyzed the SNPs in the promoter region of lncFAM200B gene and found that the SNP1 was linked with the promoter active region mutation, SNP2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal breeding, it is important to explore crucial markers. In cattle, numerous variations have been identified within the protein-coding genes, but only a few studies have uncovered the variations in the non-coding RNA genes (Jin et al, 2018; Yu et al, 2018). In this study, first, we analyzed the SNPs in the promoter region of lncFAM200B gene and found that the SNP1 was linked with the promoter active region mutation, SNP2.…”
Section: Discussionmentioning
confidence: 99%
“…The samples of Qinchuan cattle ( n = 139), Jinnan cattle ( n = 121), Nanyang cattle ( n = 67), and Ji’an cattle ( n = 25) were randomly collected from Shaanxi, Shanxi, He’nan, and Jiangxi provinces, respectively. The detailed information and records of body measurement traits for the cattle were the same as the published papers (Zhang et al, 2015; Jin et al, 2018). The blood DNA samples were isolated using high salt-extraction method (Aljanabi and Martinez, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Here we identified, for the first time to our knowledge, a sow prolificacy-associated variant, 19-bp duplication in the promoter region of lincRNA NORFA. In domestic animals, only a few lncRNA variants associated with important economic traits were found, including variants rs325797437, rs344501106, rs81286029, and rs318656749 in lncRNA MEG3 associated with porcine meat production traits 62 , a variant g.1263T>A in lncRNA ADNCR associated with bovine growth traits 63 , and a variant in lincRNA GDNF-AS associated with canine insensitivity to pain 64 . Overall, based on the distribution of the 19-bp duplication in pig breeds with different fertility and the expression levels of NORFA in granulosa cells from individuals with different genotypes, we identified for the first time that a candidate lincRNA for sow prolificacy, providing insights into the molecular mechanism of the high prolificacy of Erhualian pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples of Qinchuan ( n = 139) and Nanyang cattle ( n = 145) were collected from Shaanxi and Henan provinces, respectively. The data of the body measurement traits of the Qinchuan and Nanyang cattle were the same as in a previously published paper (Jin et al, 2019). The DNA samples were isolated by the high salt‐extraction method (Aljanabi & Martinez, 1997).…”
Section: Methodsmentioning
confidence: 99%